2008
DOI: 10.3727/036012908803861186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture Given at the HT 7, ST 36, ST 40 and KI3 Acupoints on Various Parts of the Brains of Alzheimer's Disease Patients

Abstract: In this study, we explore various regions of the brains of Alzheimer' s Disease (AD) patients before and after acupuncture treatment of acupoints in the brain in order to determine the effect, if any, of acupuncture on AD. Twenty-six patients with clinically-diagnosed AD underwent functional magnetic resonance imaging (fMRl) while undergoing acupuncture at the four acupoints of Shenmen (HT 7), Zusanii (ST 36), Fenglong (ST 40) and Taixi (KI 3). tMRI Block design paradigm was chosen by electroacupumcture interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 10 publications
(6 reference statements)
0
62
0
Order By: Relevance
“…Basically, acupuncture stimulation of main acupoints around the body was investigated and evaluated by different molecular imaging modalities. These studies showed that different molecular imaging techniques played important roles in such investigations (Wu et al, 1999b;Litschera and Schikora, 2002;Siedentopf et al, 2002;Lee et al, 2003;Fang et al, 2004;Nakagoshi et al, 2005;Napadow et al, 2005;Yan et al, 2005;Schlunzen et al, 2007;Deng et al, 2008;Lin et al, 2008;Qin et al, 2008;Vas et al, 2008;Zhou and Jin, 2008;Harris et al, 2009;Ho et al, 2009;Kong et al, 2009;Lai et al, 2009;Liu et al, 2009;Sato et al, 2009;Bai et al, 2010;Hsieh et al, 2011).…”
Section: Basic Acupuncture Techniques Assessed With Molecular Imagingmentioning
confidence: 96%
“…Basically, acupuncture stimulation of main acupoints around the body was investigated and evaluated by different molecular imaging modalities. These studies showed that different molecular imaging techniques played important roles in such investigations (Wu et al, 1999b;Litschera and Schikora, 2002;Siedentopf et al, 2002;Lee et al, 2003;Fang et al, 2004;Nakagoshi et al, 2005;Napadow et al, 2005;Yan et al, 2005;Schlunzen et al, 2007;Deng et al, 2008;Lin et al, 2008;Qin et al, 2008;Vas et al, 2008;Zhou and Jin, 2008;Harris et al, 2009;Ho et al, 2009;Kong et al, 2009;Lai et al, 2009;Liu et al, 2009;Sato et al, 2009;Bai et al, 2010;Hsieh et al, 2011).…”
Section: Basic Acupuncture Techniques Assessed With Molecular Imagingmentioning
confidence: 96%
“…Typical examples are explanations for pain relief, 1,2 torticollis therapy, 3 and treatments recommended for blood pressure 4 and asthma-related diseases. 5 More recently, 7 there has been some interest in treating Alzheimer's disease (AD), currently an almost epidemic neurodegenerative disease, with the help of the electroacupuncture technique, and remarkable success has been reported. 7,8 AD 9 causes severe impairments related to memory, language, social abilities, mental faculties, judgment capacity, disorientation in time and space, limitations in visual processing, and general coherent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…5 More recently, 7 there has been some interest in treating Alzheimer's disease (AD), currently an almost epidemic neurodegenerative disease, with the help of the electroacupuncture technique, and remarkable success has been reported. 7,8 AD 9 causes severe impairments related to memory, language, social abilities, mental faculties, judgment capacity, disorientation in time and space, limitations in visual processing, and general coherent behavior. It is an inexorable chronic and progressive disease characterized by the loss of neurons in certain parts of the brain, which starts decades before the appearance of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is a therapy of Traditional Chinese Medicine that promotes the recovery of neural function without toxic side effects and has attracted significant domestic and international attention recently. Previous studies have found that Electro Acupuncture (EA) has been used for the treatment of spinal cord injury as it has been shown to significantly improve traumatic paralysis [9,10]. But there is little report on the treatment of spinal cord injury by elongated needle therapy.…”
Section: Introductionmentioning
confidence: 99%